Freeze-out radii extracted from three-pion cumulants in pp, p–Pb and Pb–Pb collisions at the LHC - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Klein, Jochen; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Physics letters, 2014)
In high-energy collisions, the spatio-temporal size of the particle production region can be measured using the Bose-Einstein correlations of identical bosons at low relative momentum. The source radii are typically extracted using two-pion correlations, and characterize the system at the last stage of interaction, called kinetic freeze-out. In low-multiplicity collisions, unlike in high-multiplicity collisions, two-pion correlations are substantially altered by background correlations, e.g. mini-jets. Such correlations can be suppressed using three-pion cumulant correlations. We present the first measurements of the size of the system at freeze-out extracted from three-pion cumulant correlations in pp, p-Pb and Pb-Pb collisions at the LHC with ALICE. At similar multiplicity, the invariant radii extracted in p-Pb collisions are found to be 5-15% larger than those in pp, while those in Pb-Pb are 35-55% larger than those in p-Pb. Our measurements disfavor models which incorporate substantially stronger collective expansion in p-Pb as compared to pp collisions at similar multiplicity.
*ALICE Collaboration: B. Abelev, V. Anguelov, O. Busch, P. Glässel, J. Klein, D. Lohner, X.-G. Lu, A. Maire, J. Mercado Pérez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J. Stiller, S. Vallero, M. Völkl, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und 920 weitere Personen]
Gesehen am 06.10.2020